The Ancient Near East an encyclopedia for students - Wallenfels, Ronald; Sasson, Jack M. (Scribner, 2000)
Provides an overview of Egypt, Mesopotamia, Iran/Persia, the Arabian Peninsula, spanning over 4000 years from the Early Bronze Age to 325 B.C.E.